Renal function impairment in cervical cancer patients treated with cisplatin-based chemoradiation: A review of medical records in a Zimbabwean outpatient department - Manyau, Pinky M. C. (PLoS One, 2021)
BACKGROUND: There is a potential increase in risk of renal function impairment among patients with invasive cervical cancer (ICC) who are HIV-positive and treated with cisplatin-based concurrent chemoradiation (CCRT). This concern is due to overlapping nephrotoxicity of the drugs, and nephropathy from the diseases themselves. There is limited literature available for the short-term renal outcomes for HIV-positive patients with ICC during routine clinical management. This study aimed to assess if HIV-infection increased the risk of renal impairment in ICC patients treated with CCRT, and explore the respective risk factors. MATERIALS AND METHODS: This was a retrospective review of records of ICC patients treated with at least one cycle of weekly cisplatin during CCRT at the Parirenyatwa Radiotherapy Center from January 2017-December 2018. The RIFLE criteria were used to classify renal impairment. Analyses were performed with Fisher’s Exact tests, Wilcoxon rank sum tests. Odds ratios (OR) were generated using logistic regression. All statistical tests were 2-sided at a 5% level of significance. RESULTS: Seventy-two eligible patients were identified, 32 (44.44%) were HIV-positive. HIV-positive patients were younger (p = 0.002), had lower albumin levels (p = 0.014) and received lower cisplatin doses (p = 0.044). The mean percent reduction in estimated glomerular filtration rate (eGFR) from baseline was -19% (95% CI: -25.9% to -13.2%) for all patients. Thirty-one (43.1%) patients experienced renal impairment, 50% and 37.5% of HIV-positive and -negative patients respectively (p = 0.287). HIV-infection was associated with an adjusted OR of 1.16 (95% CI 0.35–3.43, p = 0.769). Baseline eGFR< 60ml/min was the only independent predictor of renal impairment, OR 0.25 (95% CI: 0.07–0.85). Baseline eGFR<60ml/min was also associated with receipt of lower cisplatin doses (p = 0.044). CONCLUSION: HIV-infection was not associated with elevated risk of renal impairment. Patients with an eGFR<60ml/min appear to be managed more cautiously reducing their risk for renal impairment during cisplatin therapy. The high prevalence of renal impairment in this population suggests the need for optimization of pre-treatment protocols.